Three-year follow-up results of two children born from a transplanted uterus - Janota, Jan; Orlova, Ekaterina; Novackova, Marta; Chmel, Roman; Brabec, Radim; Pastor, Zlatko; Chmel, Roman (Biomedical papers, 2023)
Aims. To evaluate the 3-year follow-up results of two children delivered at our institution in 2019 from mothers with a transplanted uterus. Methods. Observational data on pregnancy outcomes, neonatal course, and growth trajectory in two children born to mothers after uterus transplantation, including 3-year follow-up and neurodevelopmental status assessed using the Bayley Scales of Infant and Toddler Development, third edition (Bayley-III). Results. Both children were born prematurely via uneventful caesarean sections, to mothers with Mayer-Rokitansky-Kuster-Hauser syndrome and a transplanted uterus. An acute caesarean section was performed in one mother because of the onset of regular uterine contractions at 34 weeks and 6 days of pregnancy; in the other mother, an elective caesarean section was performed at 36 weeks and 2 days of gestation. The children were born healthy with no congenital malformations. They had an uneventful postnatal course and showed a normal growth trajectory during 3 years of follow-up. The Bayley-III neurodevelopmental scores of both children were within the normal ranges at ages 2 and 3 years. Conclusion. Though pregnancy after uterus transplantation is associated with the risk of premature delivery, no abnormalities were observed in the neonatal course and 3-year follow-up results, including the neurodevelopmental status, of two children born prematurely to mothers with a transplanted uterus. This is the first report on neurodevelopmental outcomes in children born after uterus transplantation. More data on children born after this radical procedure of uterine factor infertility treatment are required to support our promising results.
Keywords: absolute uterine factor infertility; assisted reproduction; Bayley-III scales; neurodevelopment; uterus transplantation